The Role of Teachers in Enhancing Public Speaking Abilities among Primary School Students - Haniati, Alvina; Jaya, Patria Handung (The Indonesian Institute of Science and Technology Research, 2026)
Public speaking is a crucial skill in the 21st century, but numerous primary school students struggle to convey their opinions within a group environment. The main objective of the research was to determine which activities improve public speaking skills, the influence of instructors, and the factors influencing their capacity to introduce these activities at Muhammadiyah Purwodiningratan Primary School in Yogyakarta. The study employed a descriptive qualitative methodology, incorporating in-depth interviews and direct observation with the headteacher, two teacher-coaches, and four pupils, supplemented by documentary triangulation of activity records. Findings revealed that the principal activities, pildacil (children’s Islamic speech contest) and saritilawah (Qur’anic recitation and speech competition), served as primary channels for pupils to practise courage, fluency, and overall speaking proficiency. Teachers functioned as facilitators, motivators, and coaches by routinely encouraging classroom discourse, tailoring materials to individual pupil needs, and providing emotional support to alleviate nervousness and stage fright. Success was underpinned by institutional school support, active parental engagement, and pupils’ intrinsic motivation. The main impediments were insufficient practice time, disparities in the levels of preparedness among pupils, and variations in their initial public speaking skills. Research findings confirm that faith-based initiatives are a successful approach for developing public-speaking skills in primary school students. Effective time management and enhanced collaboration between teachers and parents are essential for guaranteeing the long-term success of comparable projects.